2009
DOI: 10.1111/j.1600-0404.1998.tb01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory deficits in amyotrophic lateral sclerosis assessed with event-related brain potentials

Abstract: Objectives ‐ Amyotrophic lateral sclerosis (ALS) has been shown to cause neuropsychological deficits. The present investigation sought to delineate memory deficits by recording cognitive event‐related potentials (ERPs). Subjects and methods ‐ Eight ALS patients and 8 matched controls were subjected to a 2‐phase recognition memory test. During the first phase words were presented consecutively on a video‐screen with one‐third of the words being repeated. The subject had to press buttons according to whether a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Although this was an experimental set up, results can be compared to the recognition test that was used in this study (RAVLT). Similar to our observations, Muente et al [50] reported a recognition deficit in patients with ALS that was related to an absent recognition associated event-related potential. Interestingly, this effect was not observed in patients with Alzheimer's Disease which completed a comparable task [54].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although this was an experimental set up, results can be compared to the recognition test that was used in this study (RAVLT). Similar to our observations, Muente et al [50] reported a recognition deficit in patients with ALS that was related to an absent recognition associated event-related potential. Interestingly, this effect was not observed in patients with Alzheimer's Disease which completed a comparable task [54].…”
Section: Discussionsupporting
confidence: 92%
“…However, given the results yielded in the present study, memory deficits in ALS seem to be disease specific and can be differentiated from other neurodegenerative diseases such as AD when assessed specifically. Recognition deficits in patients with ALS were found the most obvious memory deficit and have been reported before [17,50], although such deficits have been mostly associated with executive dysfunction [17,29]. In our cohort, executive impairment could only account for 20.5% of memory performance in ALS, which supports the emerging notion that executive function is only one of several cognitive domains impaired in ALS [7,16].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…63,64 Memory problems involve primarily immediate recall, 49,65 but visual memory also has been implicated. 53,66 In a cohort of 146 sporadic MND cases, 20% of the patients performed below cut off (5th percentile) on the California Verbal Learning Test, with difficulties on the free recall learning trials, meanwhile on the Delayed Verbal Recognition Memory Test the performance was good.…”
Section: Memorymentioning
confidence: 99%
“…[16] "Furthermore, a study using event-related brain potentials revealed that recognition memory deficiencies were caused by poor encoding rather than poor retention over time, which is consistent with a frontal lobe interpretation." [17] "The findings show no evidence of faster forgetting in patients than in controls, but they do point to a problem with initial information assimilation. These memory results, along with those from previous investigations, are consistent with an interpretation based on poor encoding mechanisms as a result of frontal lobe dysfunction.…”
Section: Cognitive Change In Motor Neuron Disease Brain-behavior Rela...mentioning
confidence: 72%